Distributions of aluminium, cobalt, iron and manganese in the surface sediments of east coast of Peninsular Malaysia - Siti Nurul Hidayu, M. A; Asamuddin, A. H; Sabuti, A.A; Saili, N.A.B; Mohamed, C.A.R (University Kebangsaan Malaysia, 2012)
Surface sediments samples from 30 stations at the east coast of Peninsular Malaysia were collected using the Smith McIntyre grab on June 2008 in order to determine the contents of selected trace metals using the Inductive Coupled Plasma- Mass Spectrometry (ICP-MS). The concentrations of Al, Fe, Co and Mn ranged from 0.96 %-5.74 %, 6.20-8.95 %, 83-155 μg g-1 and 404-1350 μg g-1 respectively. The variation was then studied by ANOVA, which showed a significant difference for the concentrations of all elements at all sampling stations. The correlation between elements was significant (p>0.05) at all stations. Whereas, the geoaccumulation index proved that the surface sediment taken at all stations were unpolluted with Al and Mn (Class 1), moderately polluted with Fe (Class 2) and strongly polluted with Co (Class 4).